Practice_Homework_Prob_Sol_EE210_Ch-9

Practice_Homework_Prob_Sol_EE210_Ch-9 - CHAPTER 9 PROBLEM...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: CHAPTER 9 PROBLEM SOLUTIONS SOLUTION TO PROBLEM 9.1. If we can compute expressions for K and q that are real, then these quantities exist by construction. Consider that A, B, K and q must satisfy the following relationship: K cos( ϖ t + θ ) = K cos( θ ) ( 29 cos( ϖ t ) +- K sin( θ ) ( 29 sin( ϖ t ) ≡ A cos( ϖ t ) + B sin( ϖ t ) Therefore K cos( θ ) = A and - K sin( θ ) = B . Consequently, K cos( θ ) ( 29 2 +- K sin( θ ) ( 29 2 = K 2 = A 2 + B 2 in which case K = A 2 + B 2 . Further, K sin( θ ) K cos( θ ) = tan( θ ) =- B A in which case θ = tan- 1- B A with due regard to quadrant. SOLUTION TO PROBLEM 9.2. For the inductor, W L ( t ) = 1 2 L ⋅ i L 2 ( t ) = 1 2 L V o C L sin 1 LC t 2 = CV 2 2 sin 2 1 LC t and for the capacitor, W C ( t ) = 1 2 C ⋅ v C 2 ( t ) = 1 2 C V o cos 1 LC t 2 = CV 2 2 cos 2 1 LC t . Hence, W C + W L = 1 2 C ⋅ v C 2 ( t ) + 1 2 L ⋅ i L 2 ( t ) = CV 2 2 sin 2 1 LC t + cos 2 1 LC t = CV 2 2 SOLUTION TO PROBLEM 9.3. Since x ( t ) = ( K 1 + K 2 t ) e-α t , x ' ( t ) = - α ⋅ K 1 e-α t + K 2 e-α t- α ⋅ t ⋅ K 2 e-α t and x ' ' ( t ) = α 2 ⋅ K 1 e-α t- α ⋅ K 2 e-α t- α ⋅ K 2 e-α t + α 2 ⋅ t ⋅ K 2 e-α t Substituting into the differential equation, we have α 2 ⋅ K 1 e-α t- 2 α ⋅ K 2 e-α t + α 2 ⋅ t ⋅ K 2 e-α t + 2 α - α ⋅ K 1 e-α t + K 2 e-α t- α ⋅ t ⋅ K 2 e-α t [ ] + α 2 K 1 e-α t + K 2 te-α t [ ] = This means that the solution form satisfies the differential equation. SOLUTION TO PROBLEM 9.4. (a) Suppose x ( T ) = at some T. Then K 1 e s 1 T = - K 2 e s 2 T . Since e s i T whenever s i is real and T is finite, K 1 & K 2 must have opposite signs. (b) For this we solve for T and show there can only be one solution. Since K 1 e s 1 T = - K 2 e s 2 T and e s i T , K 1- K 2 = e s 2 T e s 1 T implies l n K 1- K 2 = l n e s 2 T e s 1 T = s 2- s 1 ( 29 T Hence the unique solution is given by T = l n K 1- K 2 s 2- s 1 ( 29 provided s 2 ≠ s 1 which is the case for distinct roots. SOLUTION TO PROBLEM 9.5. Suppose x ( T ) = at some T >0. This is true if and only if K 1 e s 1 T = - K 2 Te s 1 T (*) Since e s 1 T and T > 0, (*) is true if and only if K 1 = - K 2 T which is true if and only if K 1 & K 2 have opposite signs. SOLUTION 9.6 . (a) Denote one period of oscillation by T. Then by definition 9950 T = 2 π . Hence, T = 0.63148 ms. The time constant of decay is 1 ms. Therefore, NT = N × 0 . 6 3 1 4 8 = . Hence N = 1.5836 cycles....
View Full Document

{[ snackBarMessage ]}

Page1 / 68

Practice_Homework_Prob_Sol_EE210_Ch-9 - CHAPTER 9 PROBLEM...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online